Changes in pharyngeal airway dimensions following incremental and maximum bite advancement during Herbst-rapid palatal expander appliance therapy in late adolescent and young adult patients: a randomized non-controlled prospective clinical study - Amuk, Nisa Gul; KURT, GÖKMEN; KURT, GÖKMEN; Baysal, Asli; Turker, Gokhan (My University, 2019)
Objectives: This was a parallel, assessor-blinded, randomized, non-controlled prospective trial with the objective to evaluate and compare the effects of maximum advancement (MA) and incremental advancement (IA) of mandible with cast-splint-type Herbst-rapid palatal expander (RPE) appliance on pharyngeal airway dimensions and hyoid bone position in skeletal Class II late adolescents and young adults.